A study illustrating the risk factors, clinical presentation and management of ectopic pregnancy in a secondary hospital in Bahrain - Shaltout, Ola; Deen, Fatema Waheed Akbar Mohammed Akbar Nawab; Mustafa, Nawal Usman; Desouky, Marawan Mohamad ElSayed Mohamed; Gupta, Alka; Jeddy, Rafiea (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Assess the risk factors, clinical presentation and type of intervention indicated in ectopic pregnancies at American mission hospital in Bahrain. Methods: This is a retrospective cohort study conducted from August 2021 to April 2022 at American mission hospital in Bahrain. All patients (n=205) who attended the hospital from January 2017 to June 2021 with a presentation suggestive of ectopic pregnancy were extracted from the electronic medical record database and reviewed. Data was recorded on Microsoft Excel version 16.61.1 and numerical data was extrapolated into graphs and tables via IBM SPSS Statistics version 28.0.0.0 (190). Data was subjected to descriptive and stratification analysis. Results: The leading risk factor for ectopic pregnancy was previous pelvic surgery (40.4%). The most reported symptom was amenorrhea (65.9%). Risk of rupture was tripled when serum B-hCG level was elevated, rendering it the strongest predictor of rupture according to our data (95% CI=1.25, 7.19; p-value 0.0139). Majority of patients (56.4%) were treated with methotrexate with a success rate of 88.7% and 8.5% of cases were managed expectantly. Those who failed medical management or presented with rupture were treated surgically. Conclusions: Our study found B-hCG levels to be the most sensitive predictor of rupture and need for surgical intervention. Therefore, management was largely, but not exclusively, based on B-hCG levels. Majority of cases were treated medically and patients undergoing expectant management experienced no complications.